Does Ventriculoperitoneal Shunting Improve Thyroid Hormone Levels in Hydrocephalic Newborns? - Ucler, Necati; Erol, Fatih Serhat; Ozturk, Sait; Akgun, Bekir; Kaplan, Metin; Sen, Yasar (Karger, 2017)
Objective/Aim: The aim of this report was to investigate the effect of ventriculoperitoneal shunt insertion for the treatment of hydrocephalus on thyroid hormones in the first 3 months of life. Methods: Thyroid-stimulating hormone (TSH), free T3 (fT3), and free T4 (fT4) levels were compared at 7 days (preoperatively) and at 30 and 90 days (postoperatively) after birth between 25 ventriculoperitoneal shunt-inserted hydrocephalic newborns and 20 healthy newborns. Results: The TSH level at 7 days was higher in the hydrocephalic patient group (6.33 mu IU) compared to the control group (3.76 mu IU). This value was significantly decreased at 90 days in the ventriculoperitoneal shunt-inserted newborns (2.35 mu IU) compared to the control group (3.33 mu IU; p < 0.05). There were no significant differences between time points for fT4 and fT3 values in the patient group or for TSH, fT4, and fT3 values in the control group. Conclusion: We propose that a ventriculoperitoneal shunt inserted in the early period of life may have beneficial effects on thyroid hormones. (C) 2016 S. Karger AG, Basel
Keywords: Hydrocephalus; Hypothyroidism; Thyroid hormones; Ventriculoperitoneal shunt